Assessment of land use and land cover (LULC) and vegetation degradation state from wildfire within the scope of forest landscape restoration (FLR) in Cameroon - Kueshi Sémanou Dahan; Hamza Moluh Njoya; Shibire Bekele Eshetu; Kossi Hounkpati; Harifidy Rakoto Ratsimba; Stefan Sieber; Katharina Löhr (European Journal of Remote Sensing)
Forest-Savannah transition zones are increasingly vulnerable due to their position between the savannah and forest ecosystems, and their ecological and biophysical characteristics. This study evaluates the spatiotemporal dynamics of land use and land cover (LULC), degradation, and wildfire links. Random Forest (RF) classifier was used in Google Earth Engine (GEE) with Landsat 7 and 8 imageries (2001, 2015, 2023), high-quality LULC maps were produced with spectral indices. The classifier demonstrated accuracies ranging from 83% to 96%, supported by F1-Score, Precision, and Recall metrics. Overall, Wooded Land and Gallery Forest increased by 35.29%, followed by Savanna Grassland and Farmland (16.2%). Conversely, Rock Outcrop declined by 23.6%, while Bare and Built-Up Areas, Dense Forest, Water Bodies, and Mosaic Forest-Savannah decreased by 13.7%, 6.9%, 4%, and 3.7%, respectively. Savannah and farmland areas were the most burned (30–36%), followed by 25 Wooded Land (21–24%) and Dense Forest (10–14%). Savannah areas also experienced the highest fire frequency (19 events). Fire occurrence was higher in areas with low vegetation cover than densely vegetated areas and conservation zones. Savannah and farmland remained the most degraded and fire-prone. An improved monitoring approach is needed for reduction and mitigation to avoid irreversible degradation caused by wildfire.